β-D-glucan inhibits endocrine-resistant breast cancer cell proliferation and alters gene expression - JAFAAR, ZAINAB M.T. (D.A. Spandidos, 2014)
Endocrine therapies have been successfully used for breast cancer patients with estrogen receptor α (ERα) positive tumors, but ∼40% of patients relapse due to endocrine resistance. β-glucans are components of plant cell walls that have immunomodulatory and anticancer activity. The objective of this study was to examine the activity of β-D-glucan, purified from barley, in endocrine-sensitive MCF-7 versus endocrine-resistant LCC9 and LY2 breast cancer cells. β-D-glucan dissolved in DMSO but not water inhibited MCF-7 cell proliferation in a concentration-dependent manner as measured by BrdU incorporation with an IC(50) of ∼164±12 μg/ml. β-D-glucan dissolved in DMSO inhibited tamoxifen/endocrine-resistant LCC9 and LY2 cell proliferation with IC(50) values of 4.6±0.3 and 24.2±1.4 μg/ml, respectively. MCF-10A normal breast epithelial cells showed a higher IC(50) ∼464 μg/ml and the proliferation of MDA-MB-231 triple negative breast cancer cells was not inhibited by β-D-glucan. Concentration-dependent increases in the BAX/BCL2 ratio and cell death with β-D-glucan were observed in MCF-7 and LCC9 cells. PCR array analysis revealed changes in gene expression in response to 24-h treatment with 10 or 50 μg/ml β-D-glucan that were different between MCF-7 and LCC9 cells as well as differences in basal gene expression between the two cell lines. Select results were confirmed by quantitative real-time PCR demonstrating that β-D-glucan increased RASSF1 expression in MCF-7 cells and IGFBP3, CTNNB1 and ERβ transcript expression in LCC9 cells. Our data indicate that β-D-glucan regulates breast cancer-relevant gene expression and may be useful for inhibiting endocrine-resistant breast cancer cell proliferation.